Inhibition of neutral amino acid transport across the human blood-brain barrier by phenylalanine - Shulkin, B L; Betz, A L; Koeppe, R A; Agranoff, B W (Journal of neurochemistry, 1995)
The delivery of large neutral amino acids (LNAAs) to brain across the blood-brain barrier (BBB) is mediated by the L-type neutral amino acid transporter present in the membranes of the brain capillary endothelial cell. In experimental animals, the L-system transporter is saturated under normal conditions, and therefore an elevation in the plasma concentration of one LNAA will reduce brain uptake of others. In this study, we used positron emission tomography (PET) to determine the effect of elevated plasma phenylalanine concentrations on the uptake of an artificial neutral amino acid, [11C]-aminocyclohexanecarboxylate ([11C]ACHC), in human brain. PET scans were performed on six normal male subjects after an overnight fast and again 60 min after oral administration of 100 mg/kg of phenylalanine. The plasma phenylalanine concentration increased by an average of 11-fold between the first and second scans. This increase produced a reduction in [11C]ACHC uptake in all brain regions but not in scalp. The mean +/- SD influx rate constant for whole brain decreased after phenylalanine ingestion from 0.036 +/- 0.002 to 0.019 +/- 0.004 ml/g/min. Kinetic analysis of the effect of plasma phenylalanine concentration on the rate of [11C]ACHC uptake is compatible with a model of competitive inhibition so that large increases in the concentration of one LNAA in plasma will reduce the brain uptake of other LNAAs across the human BBB.